The iTreAD project: a study protocol for a randomised controlled clinical trial of online treatment and social networking for binge drinking and depression in young people. (December 2015) - Kay-Lambkin, F.; Baker, A.; Geddes, J.; Hunt, S.; Woodcock, K.; Teesson, M.; Oldmeadow, C.; Lewin, T.; Bewick, B.; Brady, K.; Spring, B.; Deady, M.; et al.
Abstract Background Depression and binge drinking behaviours are common clinical problems, which cause substantial functional, economic and health impacts. These conditions peak in young adulthood, and commonly co-occur. Comorbid depression and binge drinking are undertreated in young people, who are reluctant to seek help via traditional pathways to care. The iTreAD project (internet Treatment for Alcohol and Depression) aims to provide and evaluate internet-delivered monitoring and treatment programs for young people with depression and binge drinking concerns. Methods Three hundred sixty nine participants will be recruited to the trial, and will be aged 18–30 years will be eligible for the study if they report current symptoms of depression (score 5 or more on the depression subscale of the Depression Anxiety Stress Scale) and concurrent binge drinking practices (5 or more standard drinks at least twice in the prior month). Following screening and online baseline assessment, participants are randomised to: (a) online monthly self-assessments, (b) online monthly self-assessments + 12-months of access to a 4 week online automated cognitive behaviour therapy program for binge drinking and depression (DEAL); or (c) online monthly assessment + DEAL + 12-months of access to a social networking site (Breathing Space). Independent, blind follow-up assessments occur at 26, 39, 52 and 64-weeks post-baseline. Discussion The iTreAD project is the first randomised controlled trial combining online cognitive behaviour therapy, social networking and online monitoring for young people reporting concerns with depression and binge drinking. These treatments represent low-cost, wide-reach youth-appropriate treatment, which will have significantly public health implications for service design, delivery and health policy for this important age group. Trial registration Australian and New Zealand Clinical Trials RegistryACTRN12614000310662 . Date registered 24 March 2014.